Degradation kinetics of clavulanic acid in fermentation broths at low temperatures (2019)
ABSTRACT: Clavulanic acid (CA) is a β-lactam antibiotic inhibitor of β-lactamase enzymes, which confers resistance to bacteria against several antibiotics. CA is produced in submerged cultures by the filamentous Gram-positive bacterium Streptomyces clavuligerus; yield and downstream process are compromised by a degradation phenomenon, which is not yet completely elucidated. In this contribution, a study of degradation kinetics of CA at low temperatures (−80, −20, 4, and 25 ◦C) and pH 6.8 in chemically-defined fermentation broths is presented. Samples of CA in the fermentation broths showed a fast decline of concentration during the first 5 h followed by a slower, but stable, reaction rate in the subsequent hours. A reversible-irreversible kinetic model was applied to explain the degradation rate of CA, its dependence on temperature and concentration. Kinetic parameters for the equilibrium and irreversible reactions were calculated and the proposed kinetic model was validated with experimental data of CA degradation ranging 16.3 mg/L to 127.0 mg/L. Degradation of the chromophore CA-imidazole, which is commonly used for quantifications by High Performance Liquid Chromatography, was also studied at 4 ◦C and 25 ◦C, showing a rapid rate of degradation according to irreversible first-order kinetics. A hydrolysis reaction mechanism is proposed as the cause of CA-imidazole loss in aqueous solutions.